Enlarged fistulotomy of the papilla as access to the biliary tract during ERCP - Alexandre Gomes; Ana Sarah Rafka Haidar; Giovani Caetano Padilha; Juliana Bara; Mariana Sussai Nonato; José Mauro da Silva Rodrigues; Pérsio Campos Correia Pinto; Ricardo de Oliveira Ayres; Ronaldo Antonio Borghesi (BMC Gastroenterology, 2023)
Abstract Background Demonstration of access to the bile duct through Enlarged Papillary Fistulotomy, a method different from conventional fistulotomy. Aims Demonstration of the EFP technique with dissection in layers of the papilla for accessing the common bile duct, its efficiency and safety, rescue of cases of failure in cannulation and cases of access failure by EFP in the first attempt, facilitating cannulation in the second attempt. Methods Cross-sectional study, with retrospective data collection from 2233 ERCP exams with 528 EFP procedures, analysis of success and complications. Results 528 patients underwent EFP on the first attempt, with success in 465 cases (88.06%) and 63 failures (11.94%). Of these failures, 33 patients (52.38%) returned for a second EFP attempt, with success in 30 cases (90.9%) and failure in 3 cases (9.1%). Deep bile duct cannulation was achieved in 93.75% of EFP procedures, and cannulation failure occurred in 33 cases (6.25%). Conclusion EFP showed efficiency in CBD cannulation, did not induce post-ERCP pancreatitis, no cases of perforation or false tract, but resulted in higher rates of minor bleeding, rescued cases of access failure by EFP, facilitated the posterior approach on the second attempt, it is safe, effective, low risk and associated with few comorbidities.